Peran Efikasi Diri terhadap Penyesuaian Akademik Mahasiwa Tahun Pertama - Roida Hazima; Rudi Cahyono (PT. Penerbit Tiga Mutiara, 2024)
Self-efficacy, an individual's belief in their ability to achieve academic success, plays a crucial role in the academic adjustment of new students facing the transition from high school to university. The university environment, which is full of academic and social demands, requires good self-adjustment for students to cope with pressures and achieve academic performance. This study aims to identify the influence of self-efficacy on academic adjustment through a systematic literature review by analyzing journal articles from the last five years obtained from electronic databases such as Science Direct, ProQuest, Springer Link, and Google Scholar. From this search, six journals relevant to the research theme were identified. The review results indicate that five journals show a direct relationship between self-efficacy and academic adjustment, while one journal shows an indirect involvement. In conclusion, self-efficacy significantly helps new students adjust to the academic and social challenges at the university, which in turn enhances academic performance and reduces stress. This study highlights the importance of studying new students and using a systematic literature review to investigate the relationship between self-efficacy and academic adjustment, which has not been widely discussed in previous research.